Example of rational inequalities, Algebra

Solve (3x+ 1/ x + 4 ) ≥ 1.

Solution

The first thing that we have to do here is subtract 1 from both of sides and then get everything in a single rational expression.

 (3x + 1/ x + 4) -1 ≥ 0

(3x + 1/x+4) - (x + 4/x+4) ≥ 0

 (3x +1 - ( x + 4))/ x + 4  ≥ 0

2 x - 3 / x + 4 ≥ 0

In this case there is no factoring to do thus we can go straight to recognizing where the numerator & denominator are zero.

numerator : x = 3/2                         denominator : x = -4

Following is the number line for this problem.

322_Rational Inequalities.png

Okay, we desire values of x that give positive and/or zero in the rational expression. It looks like the outer two regions as well as x = 3/2        .  As with the first instance we will have to avoid x = -4 since that will give a division by zero error.

Then the solution for this problem is,

-∞ < x < -4    and            3/2 ≤ x < ∞

( -∞, -4)       and         [3 , ∞ )

Posted Date: 4/6/2013 5:33:32 AM | Location : United States







Related Discussions:- Example of rational inequalities, Assignment Help, Ask Question on Example of rational inequalities, Get Answer, Expert's Help, Example of rational inequalities Discussions

Write discussion on Example of rational inequalities
Your posts are moderated
Related Questions


how do i do the fundamental counting principe

Miscellaneous Functions The importance of this section is to introduce you with some other functions that don't really need the work to graph that the ones which we've looked

We should graph a couple of these to make sure that we can graph them as well. Example : Sketch the graph of the following piecewise function. Solution Now while w


In previous section we looked at the two functions  f ( x) = 3x - 2 and g ( x )= x/3 + 2/3 and saw that                                          ( f o g ) ( x ) =(g o f )( x ) =


Sketch the graph of P ( x ) = 5x 5 - 20x 4 + 5x 3 + 50x2 - 20x - 40 . Solution We set up the zeroes & multiplicities of this polynomial in the previous section hence

what are the steps to solving a variable like this one -3f=g for f